rn for some constant r, r must be a root of the characteristic equation p2 - C1p - C2 = 0. That is, r must satisfy the characteristic equation.
To prove this, first assume an = rn for a constant r. Plugging this into a given recurring relation gives:
rn = C1rn-1 + C2rn-2
Expanding the right-hand side, we get:
rn = C1r(n-1) + C2r(n-2)
Simplifying by combining equal terms, we get:
rn - C1rn-1 - C2rn-2 = 0
This is a linear homogeneous recurrence relation of degree 2 with constant coefficients. In general, solutions to such recurrence relations are of the form an = ar1n + br2n. where r1 and r2 are the roots of the characteristic equation p2 - C1p - C2 = 0.
Therefore, if an = rn for some constant r, r must be a root of the characteristic equation p2 - C1p - C2 = 0. That is, r must satisfy the characteristic equation. This completes the proof.
Learn more about Linear homogenous recurrence on brainly.com/question/29858436
#SPJ4